Assessment of the Safe Evacuation of People in the Case of Fire and Other Emergencies in Religious Places-Mosques on the Base of Scientific Calculations - Sodikov, A. N.; Yakubov, U. A. (European Journal of Life Safety and Stability (2660-9630), 2022)
This article provides information on the number of fires and emergencies in religious places in the world over the past decade, as well as the risk of fires and emergencies that can occur in these places. There are also calculations on the timing of the safe evacuation of people from the mosque building during emergencies.